Beyond Raising Awareness : Promoting Handwashing in Nepal Amid COVID 19 Crisis - World Bank (World Bank, Washington, DC, 2020)
This report proposes a simple framework for policy actions to effectively promote handwashing in Nepal amid the COVID 19 (coronavirus) pandemic. Raising awareness about proper handwashing is the cheapest, easiest and most important way to prevent the spread of the coronavirus, but it is far from sufficient in Nepal. Nepali population can be categorized into three groups based on handwashing practices. Close to half of the population in Nepal already have a fixed location for handwashing as well as soap and water. Raising awareness through media outlets will be most effective for this group. More than 30 percent have a handwashing location but without soap or water. SMS alerts coupled with media campaigns may be necessary as 20 percent of this group do not use radio, TV, newspaper or Internet but more than 95 percent of them own a mobile phone. Providing or subsidizing soaps may also be necessary. The remaining 20 percent do not have a dedicated place for handwashing, water, or soap. This group, who tend to be poorer and harder to reach by media outlets, needs the greatest policy intervention as they face more difficulties to practice handwashing but can still become the nexus of the viral infection as half of them live in urban areas. Besides the immediate benefits of preventing coronavirus infections, promoting regular handwashing can have many benefits including reduction in acute respiratoryinfections, diarrhea, substantial reduction in neonatal infections, and overall improved socio-economic outcomes in the long run. Policy interventions should consider these benefits of improving handwashing practices in this disadvantaged group.